Performance analysis of XML-binary format - Woo, Song Quan. (2010)
XML (Extensible Markup Language) is a structured document format which is used to represent the information for exchange and also the metadata encapsulating its meaning. XML is used for interoperable data representation as it is able to provide flexible and simplicity in representing tree-structured data that is human-readable.